International Remittances and Women's Reproductive Health Care: Evidence from Pakistan - Tahir Mahmood; Ramesh Kumar; Asad Ur Rehman; Sathirakorn Pongpanich (Taylor & Francis Group, 2022)
ABSTRACTThis paper determines the effect of international remittances on the healthcare utilization of childbearing mothers in Pakistan using the Pakistan Social and Living Standards Measurement (PSLM) survey, 2018-19. The study reports a significant and positive effect of international remittances on the healthcare outcomes of childbearing mothers. Importantly, the remittance-receiving households have 0.615, 0.208 and 0.306 times the odds of the non-receiving households, utilizing prenatal healthcare, postnatal healthcare, and healthcare decision making, respectively, and all of them are statistically significant. Consequently, the analysis confirms that remittance receiving-households do in fact influence and increase the likelihood of utilizing prenatal healthcare, postnatal healthcare and decisions about medical treatment for women. As regression-based estimation of remittances is prone to selection bias due to the nature of the non-experimental data set, we also used propensity score matching methods, which also confirmed a significant and positive effect of international remittances on healthcare outcomes of the childbearing mothers. Thus, financial support or social development programs by the government or non-governmental organization are pivotal in enhancing the healthcare outcomes and ultimately the living standards of childbearing mothers.